INDIGENOUS PEOPLES AND BRAZILIAN LAW: BRIEF CONSIDERATIONS ABOUT LEGISLATIVE COLONIALITY: (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
The main objective of this study is to understand the development of Brazilian legislation regarding indigenous peoples and to envision the possibility of realizing the rights conquered throughout history. Methodologically, this is a bibliographical and hypothetical-deductive research that seeks to answer the following question: How did colonial thought construct and maintain Brazilian law? It is considered, at the end of this study, that Brazilian legislation did not take into account the existence of the other, of alterity and that the logic of coloniality remained very present at all times in the history of law in Brazil. However, there are significant advances in relation to the recognition of sociocultural diversity, just as there are setbacks in this entire context that require reflection in order to understand.